Las posmemorias: Perspectivas latinoamericanas y europeas = Les post-mémoires: Perspectives latino-américaines et européennes - Basile, Teresa (Pasados presentes; Maison des Pays ibériques ; Série Amériques, 2020)
Postmemories: Latin American and European Perspectives. Is it possible to delimit an intellectual, cultural and artistic production in Europe and Latin America, as well as a political, militant and legal praxis, proper to the After Generations? What approach to the political violence of the European and Latin American 20th century characterizes them? How do the concepts and reflections linked to the conformation of a transcultural memory (traveling memory, connective memory, diasporic memory) which establish a complex movement of interaction in the memorial debates of a globalized space operate? What theoretical premises underlie the diversity of categories that attempt to discern the complex nature of these memories: postmemory, mémoire interdite, mémoire trouée/blessée, mémoire absente, prosthetic memory, among others? What roles are rehearsed by these children, these heirs, who receive the weight of a violent history in which they have not been the protagonists and which they nonetheless rework? The stories told by these different layers of After Generations are the subject of this collective book, which brings together 28 researchers specialized in various linguistic and cultural areas to propose syntheses or case studies on "post-memories" from Argentina, Chile, Uruguay, Brazil, Peru and Central America, on the one hand, and from Spain, Italy, Portugal, Central Europe and the countries of the former Soviet bloc, on the other.